Navigating University Neutrality in Geopolitical Turmoil: Not So Simple Anymore! - de Wit, Hans; Altbach, Philip (International Higher Education, 2024)
<h3 id="political-crises-including-the-israel-hamas-conflict-and-russias-invasion-of-ukraine-have-placed-great-stress-on-universities-worldwide-how-should-they-respond-should-academic-institutions-take-positions-on-key-political-and-social-issues-or-stay-neutral-the-international-realities-of-higher-education-have-made-these-calculations-much-more-complex" data-pm-slice="1 1 []">Political crises, including the Israel-Hamas conflict and Russia’s invasion of Ukraine, have placed great stress on universities worldwide. How should they respond? Should academic institutions take positions on key political and social issues or stay neutral? The international realities of higher education have made these calculations much more complex.